Evidence on Trade and Wages in the Developing World - Robbins, Donald J.. (OECD Development Centre Working Papers, 1996)
This paper synthesizes nine in-depth developing country (LDC) studies on the impact of trade upon wages. It is traditionally assumed that in LDCs trade liberalization lowers relative wage dispersion, while raising wage dispersion in DCs. Evidence from cross-sectional household data for Argentina, Chile, Costa Rica, Colombia, Malaysia, Mexico, the Philippines, Chinese Taipei and Uruguay show: first, counter to one model in Leamer (1995), for countries with diversified trade, labor supply shifts generally shift wages. Second, liberalization was accompanied by rising relative wages and labor demand. And third, trade liberalization often increases the inflow of machinery, and may partly explain positive relative demand shifts accompanying trade liberalization ...